E-Portfolio as an Evaluative Tool for Emergency Virtual Education: Analysis of the Case of the University Andres Bello (Chile) During the COVID-19 Pandemic - Rodriguez, Rubén; Martinez-Ulloa, Lorena; Flores-Bustos, Carolina (Frontiers in Psychology, 2022)
The pandemic had serious implications for university education, specifically due to the transition from face-to-face teaching to online methodologies. This article analyzes the perception of students undergoing speech therapy from a Chilean University about the E-portfolio incorporation as an evaluative tool during the emergency virtual teaching due to the COVID-19 pandemic. From quantitative research, a survey of 38 questions based on Likert scales was applied to 108 penultimate year undergraduate students. The survey demonstrated that there is an improvement in the methodology and teaching support, as well as in the creativity and professionalism of the students.